Partial sacrectomy with en bloc tumor resection without instrumentation. What level is safe? - Štulík, Jan; Rybárová, Michaela; Hladík, Pavel; Lischke, Robert; Klézl, Zdeněk; Kaiser, Radek; Naňka, Ondřej (Brain & spine, 2025)
INTRODUCTION: En bloc sacrectomy is an extensive surgical procedure which is often the only option which provides cure. Our experience shows that, in selected cases, instrumentation is not necessary even in case of a high en bloc sacrectomy retaining the cranial part of the sacrum in situ. This creates suitable conditions for subsequent proton therapy. RESEARCH QUESTION: What level of resection is safe without reconstruction? MATERIAL AND METHODS: Between 2014 and 2023 we performed a total of 29 sacral resections for various etiologies. Patients following reconstruction of the lumbosacral region by internal fixator (3) and patient after hemicorporectomy (1) were excluded from the study. The study group comprised 25 patients, 15 men and 10 women with a mean age of 45.1 years (range, 1.7-72.2 years). The most frequent indication for surgery was chordoma (8), followed by MPNST (4), yolk sac tumor (2) and undifferentiated sarcoma (2). RESULTS: Stress fractures of the sacral stump occur in elderly patients with lower bone mineral density, or in younger patients with a higher bone mineral density who are more active when resuming their daily routine after the operation. DISCUSSION AND CONCLUSION: Instrumentation is, in our view, primarily indicated in younger and more active patients, whereas in most cases, even with lower bone mineral density, non-instrumented procedure results in sufficient stability in all levels of partial resection.
Keywords: Sacral tumor; Sacrectomy; en bloc resection; en bloc sacrectomy; Chordoma; Primary sacral tumor